PEMBIAYAAN MUDHARABAH DAN KAITANNYA DENGAN NON PERFORMING FINANCING (NPF) DAN BAGI HASIL - Sri Indah Nikensari; Dian Sugiarti; Tuty Sariwulan (Jurnal Ilmiah Econosains, 2012)
ABSTRACEconomic development in Indonesia require funding from many sources. One source of funding is from the Islamic banks in recent years experienced a very rapid expansion, both of the institution and the assets and the distribution of funds.This study aims to look at the link between non-performing financing (NPF) (X1) and the profit sharing ratio (X2) to the amount of mudharabah financing (Y) in Islamic banks and Islamic business units in Indonesia. But in the process of analysis, because of autocorrelation, then added the other explanatory variables are mudharabah financing at the previous period (X3). The results showed a significant effect of the profit sharing ratio received by the bank (X2), then the mudharaba financing at the previous period (X3) to the mudharaba financing at current period (Y), but the magnitude of the NPF last period had no significant effect to the amount of mudarabah financing at current period. The lack of effect of NPF to the meaninglessness of financing was indicated that the handling of non-performing loans (NPF) used rescheduling and reconditioning scheme and financing into qordhul hasan. Although partially NPF had no significant effect to the financing, but together these three explanatory variables have a significant impact on financing. The coefficient of determination indicates the amount of 0.991, which means that 99% more variation in the mudharaba financing can be explained by the threeexplanatory variables. Keywords: Mudharabah Financing, non performance financing, qordhul hasan, profit sharing ratio